Au nano dumbbells catalyzed the cutting of graphene oxide sheets upon plasmon-enhanced reduction. Issue 52 (10th May 2016) - Wang, Xiaotian; Zhu, Mingyun; Fu, Wanlin; Huang, Chengqian; Gu, Qing; Zeng, Tingying Helen; Dai, Yunqian; Sun, Yueming
Abstract : The excellent photothermal and photoelectrical property of Au nanodumbbells make themselves serve as pore generators on the surface of GO sheets, which both accelerate the reduction and cut the large pieces of GO sheets into small pieces. Abstract : This work presents an ultrafast and low-cost method to prepare reduced graphene oxide (RGO) by photocatalytic reduction of graphene oxide (GO) sheets with the assistance of dumbbell-like Au nanorods. Au nanoparticles are effectively loaded on the surface of GO sheets by electrostatic interaction and serve as the initiating points for the splitting of GO sheets. The existence of Au nanoparticles tremendously accelerates the process of the reducing reaction as well, in which the reduction completes in 15 min, ascribed to hot electrons generated by the localized surface plasmonic resonance (LSPR) property of Au nanorods. Interestedly, in this process, the function of Au nanorods is not limited to promoting the reduction. The more important merit is that they serve as pore generators which help to cut all of the GO sheets into small pieces. This photocatalytic method of RGO preparation provides a novel strategy in this field and creates various possibilities for future applications.